Tall story - Gourlay, Candy ([S.l.] Cacho Pub. House, 2010)
Sixteen-year-old Bernardo, who is eight feet tall and suffers from a condition called Gigantism, leaves the Philipines to live with his mother's family in London, much to the delight of his thirteen-year-old half sister Andi, a passionate basketball player.
"First published in Great Britain by David Fickling Books."
Keywords: Giants -- Fiction; Size -- Fiction; Basketball -- Fiction; Culture conflict -- Fiction; Brothers and sisters -- Fiction; London (England) -- Fiction; England -- Fiction; Philippines -- Fiction